Upaya Penanggulangan Terhadap Warga Binaan Perempuan Yang Melakukan Kekerasan - Lewaherilla, Gloria Altika Adriani; Toule, Elsa Rina Maya; Sopacua, Margie Gladies (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Women's Correctional Institutions are still physically violent among inmates.Purposes of the Research: Analyze and discuss countermeasures carried out for female inmates who commit violence against fellow female inmates.Methods of the Research: This research uses empirical juridical research type with analytical descriptive research type. The technique of collecting legal materials is by conducting library research on legal materials, namely Primary Legal Materials and Secondary Legal Materials. Legal materials analysis techniques are obtained from qualitative classification.Results of the Research: The results of this study indicate that there are female inmates who are serving their criminal period, but also commit violence between inmates. The various factors that cause violence by inmates at the Class III Ambon Women's Correctional Institution are personal problems that become a burden on the inmates' minds, so that always overshadowed by feelings of irritation, boredom, and an emotional nature, which causes emotional instability among the inmates, and the absence of intimacy and harmonious relations between the inmates. As well as efforts to handle cases of violence carried out by inmates at the Class III Ambon Women's Correctional Institution in the form of pre-emptive efforts such as independent and spiritual development, preventive efforts in the form of supervision which is divided into three shifts, repressive efforts of inmates are put in solitary confinement for 6 (six) days and delaying or eliminating certain rights in accordance with a predetermined time.